Building Inclusive Education: Models and Supporting Factors in Elementary Schools - Kinasih, Ayuning Putri Puspita Sari; Hakim, Mohammad Arif Rahman; Anggraini, Nabila Putri; Sain, Zohaib Hassan (EDUCARE: Journal of Primary Education, 2024)
Inclusive education in educational institutions still faces challenges, such as negative societal perceptions, limited teacher competencies, inadequate supporting facilities, and curricula that must be fully adaptive. This study employs a qualitative descriptive method with an embedded case study approach. Data were collected through in-depth interviews, direct observation, and document analysis, and they were validated using source and technique triangulation. The findings reveal three main aspects of the inclusive education model: 1) Student interactions, implementing a uniform curriculum, fostering empathy between regular students and students with special needs, and institutional support from teachers. 2) Infrastructure optimization, including adequate school physical conditions, classroom facilities, special provisions for students with special needs, and other supporting infrastructure. 3) Synergy among schools, parents, and resource centers to ensure collaboration in creating an inclusive learning environment. This study recommends teacher training, improved facilities for children with special needs (ABK), and the development of educational technology to support inclusive learning. Inclusive education is expected to operate more effectively and sustainably with these strategies. The contribution of this research provides an understanding of the application of inclusive education models in basic education through interactions between students supported by a uniform curriculum and teacher assistance, optimization of adaptive school infrastructure for students with special needs, and collaboration between schools, parents, and resource centers to create an inclusive learning environment.